The Role of Internal Control As a Part of Internal Audit in Implementation As the Legal Service Agency - Hasbudin, Nitri Mirosea (Jurnal Akuntansi, 2012)
Laporan ini menganalisa peran dari kontrol internal sebagai bagian dari fungsi audit